Pengaruh media pembelajaran gamifikasi terhadap minat belajar Pendidikan Pancasila siswa kelas VIII - Haryanti Sapitri; Hambali Hambali; Indra Primahardani (Departemen Pendidikan Kewarganegaraan dan Ilmu Hukum Universitas Negeri Padang, 2026)
This study was motivated by the low level of students’ learning interest in Pancasila Education due to the use of conventional and less interactive teaching methods. The purpose of this study was to determine the effect of gamification-based learning media on the learning interest of eighth-grade students at SMP Negeri 46 Pekanbaru. The research employed a quantitative approach using a true experimental design in the form of a pretest-posttest control group design. The population consisted of 201 students, with two classes selected as samples through simple random sampling, namely the experimental and control groups. Data were collected using a Likert-scale questionnaire to measure students’ learning interest. The results showed that the data were normally distributed and homogeneous. The N-Gain analysis indicated that the experimental class obtained a score of 0.66 (moderate category, quite effective), while the control class obtained a score of 0.40 (low category). Hypothesis testing using the Independent Sample t-Test showed that the calculated t-value (5.248) was higher than the t-table value (1.990) with a significance value of 0.000 < 0.05, indicating that the alternative hypothesis was accepted. Thus, it can be concluded that gamification-based learning media significantly improves students’ learning interest.